Learners in the Perspective of Islamic Education: a Review of Their Meaning and Role - Muhammad Rizky Fadhlan; Anggi Ditami Maharani; Widya Aprillia (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2024)
Islamic religious education places learners as the center in the learning process, with an important role as recipients and seekers of knowledge, experience, and religious values or life. This research aims to understand the role and meaning of learners in the perspective of Islamic Religious Education, focusing on how they actively participate in self-development according to Islamic teachings. The research method used is a qualitative literature study approach with text analysis of various relevant literature, involving the stages of data collection, reading, recording, and processing research materials. The results show that in Islamic Religious Education, students are not only as recipients of knowledge but also as active subjects who play an important role in the learning process. They are expected to develop their intellectual and spiritual potential optimally, becoming individuals of faith, piety, and noble character. Learners have the responsibility to learn throughout life, practice, and disseminate the knowledge gained, as well as act as caliphs on earth with intellectual capacity developed through education in accordance with Islamic principles.